Effect of bleaching duration of Hydrogen Peroxide on Sesbania grandiflora pulp - Loh, Chek Swee (2019)
Bleaching is the process to brighten the pulp by removing the impurities and lignin on the surface of the wood fibers. Chlorine based bleaching agent have the ability to brighten the pulp effective but it has harmful effect to the environment. Therefore, a total chlorine free bleaching agent, hydrogen peroxide is used in this research to bleach the pulp derived from Sesbania grandiflora, Turi. The purposes of this research is to identify the effects of hydrogen peroxide on Sesbania grandiflora pulp and to determine the paper properties made from this pulp under a constant temperature and concentration of hydrogen peroxide at different bleaching duration. A total of three different bleaching duration were used to bleach the Sesbania pulp, which are 20, 40 and 60 minutes under 50 °C and 3% of hydrogen peroxide. The physical, optical and mechanical properties of handsheets made from this pulp were tested according to TAPPI standard. Based on the result, the kappa number and brightness of handsheets made were significantly affected by hydrogen peroxide. The mechanical properties of the handsheets were not much influenced by the hydrogen peroxide bleaching agent. The brightness of handsheet was improved with the increasing of hydrogen peroxide bleaching duration. At the same time, the strength properties of the handsheet were also able to maintain as the bleaching duration increase.